2009
DOI: 10.1109/tbme.2009.2027692
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Timing Delays and Electrode Positions in Optimization of Biventricular Pacing: A Simulation Study

Abstract: Electrode positions and timing delays influence the efficacy of biventricular pacing (BVP). Accordingly, this study focuses on BVP optimization, using a detailed 3-D electrophysiological model of the human heart, which is adapted to patient-specific anatomy and pathophysiology. The research is effectuated on ten heart models with left bundle branch block and myocardial infarction derived from magnetic resonance and computed tomography data. Cardiac electrical activity is simulated with the ten Tusscher cell mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…For example, in a cohort of 648 virtual patients it was found that the location of the LV pacing site is an important factor in response to CRT (Crozier et al, 2016). Electrophysical cardiac computer modeling studies also demonstrated the importance of LV pacing site and the potential of simulations to predict the electrical optimal pacing location and setting (Reumann et al, 2007; Miri et al, 2009; Niederer et al, 2011). Our study shows, however, that an electrical optimum (lowest electrical dyssynchrony) might not necessarily be optimal for overall pump function.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a cohort of 648 virtual patients it was found that the location of the LV pacing site is an important factor in response to CRT (Crozier et al, 2016). Electrophysical cardiac computer modeling studies also demonstrated the importance of LV pacing site and the potential of simulations to predict the electrical optimal pacing location and setting (Reumann et al, 2007; Miri et al, 2009; Niederer et al, 2011). Our study shows, however, that an electrical optimum (lowest electrical dyssynchrony) might not necessarily be optimal for overall pump function.…”
Section: Discussionmentioning
confidence: 99%
“…12 The originality of this article lies within the inclusion of BSPM in the optimization method. Several studies tested BSPM accuracy and indicated that the estimate of the infarct location depends on the AHA subdivision.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Miri et al. [65, 87] computed biventricular-paced activation sequences and ECGs in ten patient-specific heart models to simulate the process of CRT tuning. They found that in addition to AV and VV delays, the position of the LV electrode influenced electrical synchrony and that the optimal position was patient-dependent.…”
Section: Applications Of Computer Heart Modelsmentioning
confidence: 99%